Height growth, wood density and molecular markers to distinguish five tree species of Dipterocarpaceae grown at same site (Bangladesh Journal of Scientific and Industrial Research, 2013)
The dipterocarps are of economic and ecological significance. To determine if simple traits can be used to distinguish wood of five representative species (Dipterocarpus kerrii, Hopea plagata, Parashorea malaanoman, Shorea almon and Shorea contorta), we determined tree height, wood density and chloroplastic (cp) DNA restriction patterns as a molecular fingerprint. Wood was obtained from trees of the same age grown at the same plantation (Leyte, Philippines). Data were subjected to cluster analysis (tree height, wood density) and used for the construction of a phylogenetic tree (cpDNA-PCR). Comparison of the result of cluster analysis with the phylogeny of the taxa based on cpDNA variation showed similar differentiation patterns. D. kerrii and H. plagata were always clearly separated from the other three species. Cluster analyses on tree characters revealed a clear grouping of all samples according to species, except for S. contorta, which was partly mixed with the subcluster of P. malaanoman. Since the formation of clades obtained by cpDNA-PCR analysis of samples was similar to that found by cluster analysis, our data indicate that wood traits can be used for taxonomic purposes to distinguish distantly related tree species of the same family. Bangladesh J. Sci. Ind. Res. 47(4), 407-414, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14070